2011
DOI: 10.4329/wjr.v3.i2.47
|View full text |Cite
|
Sign up to set email alerts
|

Use of carbon dioxide as negative contrast agent for magnetic resonance cholangiopancreatography

Abstract: AIM:To evaluate the effects of using CO2 as negative contrast agent in decreasing the overlapping on the pancreaticobiliary system from intestinal fluids. METHODS:We evaluated the magnetic resonance cholangiopancreatography (MRCP) images in 117 patients divided into two groups (group 1, without taking gas producing crystals to produce CO2, n = 64; group 2, with CO2, n = 53) in a 1.5T unit using MRCP sequence.Anatomic locations of intestinal fluids distribution, overlapping with common bile duct (CBD) and pancr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
15
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(17 citation statements)
references
References 14 publications
2
15
0
Order By: Relevance
“…The shortest fasting period provided was 3 h ( 10 ), the longest was 12 h ( 11 ) with a median 6 h ( 12 – 16 ). The administered amount of contrast agent ranged from 10 mL ( 17 ) to 1000 mL ( 18 ); two articles did not supply any information on the administered amount of oral contrast ( 19 , 20 ). In most cases (n = 11), MRCP was performed immediately after the oral ingestion ( 11 , 17 27 ).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The shortest fasting period provided was 3 h ( 10 ), the longest was 12 h ( 11 ) with a median 6 h ( 12 – 16 ). The administered amount of contrast agent ranged from 10 mL ( 17 ) to 1000 mL ( 18 ); two articles did not supply any information on the administered amount of oral contrast ( 19 , 20 ). In most cases (n = 11), MRCP was performed immediately after the oral ingestion ( 11 , 17 27 ).…”
Section: Resultsmentioning
confidence: 99%
“…The administered amount of contrast agent ranged from 10 mL ( 17 ) to 1000 mL ( 18 ); two articles did not supply any information on the administered amount of oral contrast ( 19 , 20 ). In most cases (n = 11), MRCP was performed immediately after the oral ingestion ( 11 , 17 27 ). In all other cases (n = 14), time intervals between oral administration and the beginning of the scan ranged between 5 min ( 10 , 28 , 29 ) and 180 min ( 20 ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The results of the study showed a decrease in the fluids of the antrum and the duodenal bulb, which in turn led to a decrease in the signal overlapping with the common bile duct. However, the tolerability of the bad smell and side effect of carbon dioxide made the patients uncomfortable [18].…”
Section: Introductionmentioning
confidence: 99%